Optical sensing of uric acid using uricase as bio-receptor - Liew, Jin Yee (2015)
Purines are natural substances found in body’s cells and in virtually all foods. When purine derivatives undergo metabolic breakdown, uric acid is produced. Abnormally high concentration of uric acid in the body can lead to diseases such as gout and uric acid stone formation. Thus, uric acid determination serves as a marker and plays a very important role in diagnosis. For clinical diagnosis and monitoring purposes, biosensor has been introduced as it is a fast and reliable analytical device. Demands for the current trend of biosensor development keep on increasing due to the advancement in technology especially the applications of biosensors using optical detection. In the present study, uricase from Arthrobacter globiformis was used as a bio-receptor and integrated to optical fibre for uric acid determination. Preliminary experiments of uricase immobilization techniques on glass slide were conducted before proceeding on optic fibre. Glass activation produces more reactive hydroxyl groups on the glass surface and utilization of both chitosan and glutaraldehyde as cross-linker demonstrated a better response towards uric acid. The immobilization techniques and optimum enzyme concentration obtained were then employed and proceeded on a tapered optical fibre. Uricase-immobilized tapered optic fibre with waist diameter of 80 μm and waist length of 20 mm was shown to have a positive relationship between absorbance value and concentration of uric acid range from 1.0 mM to 2.0 mM. From the results obtained, optical sensing of uric acid was possible and successful by using uricase as bio-receptor.